Verification of the Tanaka non-proportional isotropic cyclic hardening model under asynchronous loading. (1st November 2022) - Skibicki, Dariusz; Pejkowski, Łukasz; Karolczuk, Aleksander; Seyda, Jan
Abstract: Non-proportional cyclic loading path induces intrinsic strain hardening to the low stacking fault energy materials. The hardening is manifested in increased stress response which underestimation leads to non-conservative life prediction. This study aims to verify the Tanaka non-proportional isotropic cyclic hardening model under a wide spectrum of multiaxial asynchronous loadings. The Tanaka model is coupled with the Chaboche kinematic hardening model for stress path estimation. Modeling results are compared with fatigue experiments for two non-alloyed steel grades, E235 and E355. The Tanaka model improves the performance of the Chaboche model and exhibits its applicability to asynchronous loading.